EDUCATIONAL AND SOCIAL CONSTRUCTIONS OF THE SHARIA IMPLEMENTATION IN ACEH, INDONESIA - Manan, Abdul; Salasiyah, Cut Intan; Kamarullah, Kamarullah; Tathahira, Tathahira (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2023)
Abstract: The embodiment of traditional values, which were replaced by Islamic values, is strongly tied to the application of sharia in the central Aceh regency of Bener Meriah. It is interesting to note that the application of Sharia in that region involved both anthropological and social factors. This qualitative investigation looked at the application of Sharia in Bener Meriah as a social phenomenon reflected in local residents' behaviours. Purposive sampling was used to select respondents for interviews, which served as the data gathering method. The findings showed three things. First, while the government and associated organizations continue to socialize the Sharia, it is primarily about interpreting Islamic law as a punishment for lash breakers. Second, the integration of Sharia ideals into social interactions is a goal of the establishment of Sharia. In addition to the traditional values of the Gayo culture, which have a long history, locals' awareness of Sharia also plays a vital role. Accordingly, based on the findings, the Sharia implementation is effective, especially in light of the few Sharia infractions that were discovered.Keywords: Muslim communities; Public views; Sharia implementation; Social construction